Navigating Misinformation in Organizational Coaching: A Systematic Literature Review of Fake News Impact on Leadership Culture and Performance Indicators - Septien Dwi Savandha (Journal Of Social Science (JoSS), 2025)
The proliferation of digital misinformation has fundamentally altered organizational information environments, creating serious challenges for leadership development, coaching culture, and performance management systems. Despite growing research on fake news and digital communication ethics, there remains limited understanding of how misinformation directly influences organizational dynamics. This research aims to synthesize empirical and conceptual evidence on the impact of misinformation on the integrity of coaching culture, leadership authenticity, and the reliability of performance indicators. Employing a systematic literature review (SLR) based on PRISMA 2020 guidelines, data were collected from Scopus, Web of Science, ScienceDirect, and Emerald Insight, covering publications between 2013 and 2025. From an initial pool of 1,246 studies, 102 articles met the inclusion criteria after rigorous screening and quality appraisal. Data were extracted and coded using standardized templates, and thematic analysis, complemented by bibliometric mapping (VOSviewer 1.6.20), was conducted to identify major conceptual domains. Four central themes emerged: misinformation and organizational communication, leadership integrity and ethical vulnerability, the resilience of coaching culture, and the reliability of performance indicators. Results reveal that misinformation erodes trust in communication, promotes unethical leadership behavior, and distorts organizational performance data. This review integrates information integrity theory, ethical leadership frameworks, and coaching culture models to propose the concept of informational authenticity, which refers to an organization’s capacity to maintain transparent, verifiable, and ethical communication flows. Maintaining information integrity is, therefore, a strategic necessity for sustaining ethical leadership and coaching excellence in the digital era.